Urban Social Movements and the Right to the City: An Introduction to the Special Issue on Urban Mobilization - Domaradzka, Anna (Voluntas (Manchester, England), 2018)
This paper introduces the special issue and explains the diversity as well as common features of mobilization practices present in cities around the world. The paper starts with presenting the specificity and history of urban movements worldwide, as well as the development of 'right to the city' frame. Drawing on the existing literature, it focuses on presenting different forms of urban activism and interpretations of 'right to the city' slogan. This paper strives to fuse the framework of social movements as networks (Diani, in: Diani, McAdam (eds) Social movements and networks, Oxford University Press, Oxford, pp 299-318, 2003) of challengers (Gamson in The strategy of social protest, Wadsworth Publishing, Belmont, 1990) with the concepts of diffusion and translation of ideas, borrowed from Finnemore and Sikkink (Int Org 52(4):887-917, 1998). It also illustrates the application of the theoretical concepts of incumbents and challengers (Gamson 1990), organizational platform and norm life cycle (Finnemore and Sikkink 1998) as well as the development on movement networks within and between localities (Diani in The cement of civil society: studying networks in localities, Cambridge University Press, New York, 2015). The theoretical model helps to explain the rapid global spread of the notion of the 'right to the city.' The paper concludes with a discussion of the urban context, both 'giocai' and. global, as an arena of social mobilization around different aspects of the 'right to the city.'